Platelets as drivers of ischemia/reperfusion injury after stroke - Shaik, Noor F. (Blood Adv, 2021)
Ischemic stroke is a leading cause of morbidity and mortality worldwide and, despite reperfusion either via thrombolysis or thrombectomy, stroke patients often suffer from lifelong disabilities. These persistent neurological deficits may be improved by treating the ischemia/reperfusion (I/R) injury that occurs following ischemic stroke. There are currently no approved therapies to treat I/R injury, and thus it is imperative to find new targets to decrease the burden of ischemic stroke and related diseases. Platelets, cell fragments from megakaryocytes, are primarily known for their role in hemostasis. More recently, investigators have studied the nonhemostatic role of platelets in inflammatory pathologies, such as I/R injury after ischemic stroke. In this review, we seek to provide an overview of how I/R can lead to platelet activation and how activated platelets, in turn, can exacerbate I/R injury after stroke. We will also discuss potential mechanisms by which platelets may ameliorate I/R injury.